Hybridization properties of oligodeoxynucleotide pairs bridged by polyarginine peptides. - Wei, Z (1996)
The hybridization properties of a series of probes, based on two 9mer oligodeoxynucleotides (designated as I and II) having an appended oligoarginine chain (Rn) to produce peptide-oligonucleotide conjugates or peptide-bridged oligonucleotide pairs (e.g. Rn-I or II-Rn-I), were investigated. For the double-linked probes, we found that the peptide bridge induces the two 9mers to bind complementary single-stranded DNA or RNA targets with substantially enhanced thermal stability. The resulting hybrid with complementary DNA was found to assume a 1:1 complex in the B conformation as judged by UV mixing curves and CD spectroscopy. Complexes of single or double-linked probes with complementary RNA exhibited sensitivity to RNase H digestion. The influence of the identity and chirality of the repeating unit in the bridge, the length of the bridge, the gap size and the salt concentration on the hybridization properties of this new class of oligonucleotide probes was also studied. Our data reveal that these compounds exhibit properties that should prove useful in the development of antisense strategies.